Suburban Warriors The Origins of the New American Right - McGirr, Lisa 1962- (Princeton University Press, 2015)
In the early 1960s, American conservatives seemed to have fallen on hard times. McCarthyism was on the run, and movements on the political left were grabbing headlines. The media lampooned John Birchers's accusations that Dwight Eisenhower was a communist puppet. Mainstream America snickered at warnings by California Congressman James B. Utt that "barefooted Africans" were training in Georgia to help the United Nations take over the country. Yet, in Utt's home district of Orange County, thousands of middle-class suburbanites proceeded to organize a powerful conservative movement that would land Ronald Reagan in the White House and redefine the spectrum of acceptable politics into the next century.
Description based on online resource; title from PDF title page (publisher's Web site, viewed September 10 2015)
Keywords: USA -- Government; Geschichte 1945-1989; Culture and History of non-European Territories; Global History; History; Politik; Political Science / Essays; Political Science / Government / General; Political Science / Government / National; Political Science / Reference; Conservatism -- United States -- History -- 20th century; Right and left (Political science) -- History -- 20th century; United States -- Politics and government -- 1945-1989; Konservativismus; Die Rechte; USA